Cover Image. (1st February 2023) - Chen, Hongyi; Chen, Chen; Huang, Shijie; Zhao, Mengjie; Wang, Tengyue; Jiang, Taoshan; Wang, Chuanhong; Tao, Zhen; Zhang, Yan; Wang, Yunhe; Wang, Wanyi; Tang, Qingfeng; et al.
Abstract : The front cover image is based on the Original Article Inactivation of RPX1 in Arabidopsis confers resistance to Plutella xylostella through the accumulation of the homoterpene DMNT by Hongyi Chen et al., https://doi.org/10.1111/pce.14528 .